Traditional Versus Digital Note-Taking in the Knowledge Retention of Bachelor of Science in Nursing Students - Abug Sean Rabi Luis S; Bumad-Ong Genara Valerie A; Divinagracia Carol Anne A; Gabriel Bianca Lauren C; Guzman Chanelle Andrea A; Malesido Samantha Nicole O; Tolentino Accel John G; Bea Teresa S Sengco (International Journal of Advanced Multidisciplinary Research and Studies, 2026)
Students’ performance is always an issue when it comes to education, especially to their response with examinations and tests, because of that, students have formulated different types of methods in order to retain information, one of which is the note-taking methods that are diversely used by students of varying levels across the world. Note-taking methods, unlike other studying techniques that had multiple variations, only have two subtypes, Traditional Note-Taking Method and Digital Note-Taking Method. This study aims to see the difference between Traditional Note-Taking Method and Digital Note-Taking Method in terms of their effect on the knowledge retention of the students. This study used questionnaires, interviews, and pre-test and post-test in order to acquire the necessary data for the study. This study used frequency count, percentage formula, weighted mean, standard deviation, independent two tailed t-test, and paired right tailed t-test to interpret the data gathered, and to see whether there is a significant difference between the note-taking methods. The Experimental Quantitative Research was conducted at Dr. Carlos S. Lanting College which targeted 80 First Year Nursing Students, which utilized a stratified random sampling in selecting the respondents. The researchers utilized a 75-item Multiple Choice Questionnaire divided into 3 Parts: Pre-Test, Post-Test 1 or Immediate Recall and Post-Test 2 or Delayed Recall with all having 25 items, questions were also reorganized and paraphrased among the 3 Parts, the Questionnaires was used to gather necessary data and was Analyzed using Reliability, Descriptive, and Independent T-Test Analysis. Overall, The analysis revealed that there were no Significant Difference between Traditional Note Taking Method, Digital Note Taking Method, and with the Control Groups Preferred Note Taking Method and No Note Taking Method (t = 0.75, ta/2= 1.6860) suggesting that regardless of the note taking method or lack thereof will still contribute to a student’s Knowledge Retention but will ultimately vary on the Intrinsic and Extrinsic factors each individual students possess such as their attention, focus, individual intellect and ability to comprehend ideas and concepts.